Heartache or heartbreak - Howat, R. C.; Robson, M. W. (The Swimming Times, 1992)
The accuracy and precision of a swimmer's estimate of heart rate was determined. Swimmers were instructed to perform aerobic swims at threshold. They were asked to count their heart rates after a particular swim. One minute after completion of the exercise a whole blood lactic acid analysis was conducted at poolside. Swimmers were divided in seniors and age groupers. Conclusion: Using heart rates, such as those typically published to suggest a range within which a particular type of training effect will be achieved, to estimate work will roughly undertrain 33%, stimulate 33%, and overtrain 33% of swimmers in a squad for the purpose of achieving the same training effect. That means, only one in three will respond as intended. If different rates are not used for women, they will be grossly overtrained because a given heart rate needs to be less than males to have an "equivalent" intensity. Using heart rate "norms" to prescribe work intensities in swimming is more erroneous than accurate for achieving particular types of physiological response.